The Effects of Separate Facial Areas on Emotion Recognition in Different Adult Age Groups: A Laboratory and a Naturalistic Study - Faustmann, Larissa L.; Eckhardt, Lara; Hamann, Pauline S.; Altgassen, Mareike (Frontiers in Psychology, 2022)
The identification of facial expressions is critical for social interaction. The ability to recognize facial emotional expressions declines with age. These age effects have been associated with differential age-related looking patterns. The present research project set out to systematically test the role of specific facial areas for emotion recognition across the adult lifespan. Study 1 investigated the impact of displaying only separate facial areas versus the full face on emotion recognition in 62 younger (20–24 years) and 65 middle-aged adults (40–65 years). Study 2 examined if wearing face masks differentially compromises younger (18–33 years, N = 71) versus middle-aged to older adults’ (51–83 years, N = 73) ability to identify different emotional expressions. Results of Study 1 suggested no general decrease in emotion recognition across the lifespan; instead, age-related performance seems to depend on the specific emotion and presented face area. Similarly, Study 2 observed only deficits in the identification of angry, fearful, and neutral expressions in older adults, but no age-related differences with regards to happy, sad, and disgusted expressions. Overall, face masks reduced participants’ emotion recognition; however, there were no differential age effects. Results are discussed in light of current models of age-related changes in emotion recognition.